2019
DOI: 10.1038/s41598-018-35979-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoculoside, a sphingoid base-like compound from Acremonium disrupts the membrane integrity of yeast cells

Abstract: We have isolated Hypoculoside, a new glycosidic amino alcohol lipid from the fungus Acremonium sp. F2434 belonging to the order Hypocreales and determined its structure by 2D-NMR (Nuclear Magnetic Resonance) spectroscopy. Hypoculoside has antifungal, antibacterial and cytotoxic activities. Homozygous profiling (HOP) of hypoculoside in Saccharomyces cerevisiae (budding yeast) revealed that several mutants defective in vesicular trafficking and vacuolar protein transport are sensitive to hypoculoside. Staining o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Auroramycin was used at 1.56 μM which caused a 50% reduction in growth in YPD-HEPES medium after 10 hours at 30 °C. Preparation of genomic DNA from yeast cells, amplification of barcode sequences by PCR and Next Generation Sequencing (NGS) of the PCR products were all performed as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…Auroramycin was used at 1.56 μM which caused a 50% reduction in growth in YPD-HEPES medium after 10 hours at 30 °C. Preparation of genomic DNA from yeast cells, amplification of barcode sequences by PCR and Next Generation Sequencing (NGS) of the PCR products were all performed as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…Some of the 4817 mutants had a significantly high absolute logFC value. Mutants with positive logFC values in homozygous profiling assays exhibit virtually no resistance to the compound from our previous work 25 , 26 , 35 . Henceforth, we focused on DEP-sensitive mutants (i.e., mutants with logFC value < − 0.5).…”
Section: Resultsmentioning
confidence: 77%
“…Intriguingly, the relative toxicity of another phthalate diester and monoester pair is exactly the opposite. Mono(2-ethylhexyl) phthalate (MEHP) is more potent than its corresponding diester, di-(2-ethylhexyl)-phthalate (DEHP), in yeast and mammalian cells 25 , 26 . Our previous studies showed that MEHP affected plasma membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Propidium Iodide (PI) staining assay was carried out as described by Alfatah et al 29 with slight modification. Briefly, C. albicans SC5314 cells of 0.5 OD were treated with different concentration of SL along with DMSO as vehicle control in 2 mL of YPD medium at 30 °C and 200 rpm for 5 h. Further, the treated cells were washed twice and resuspended in 1× PBS.…”
Section: Methodsmentioning
confidence: 99%